INFLUENCE FRACTIONAL COMPOSITION AND TERMS OF STORAGE ON TECHNOLOGICAL PARAMETERS OF SUNFLOWER SEEDS - Волянский, Алексей; Ящук, Надежда; Гаращук, Юлия (SWorldJournal, 2021)
The technological parameters of sunflower seeds of variety Sur and hybrid NK Neoma and the influence of fractional composition and duration of storage on their change are investigated. It was found that in the first 3 months of storage there was a signifi